Does a look of fear prompt to act? The effects of gaze and face emotional expression on manipulable objects - Scerrati, Elisa; Rubichi, Sandro; Iani, Cristina (Frontiers in Psychology, 2022)
Gaze direction is an important social cue for understanding the intentions of other people. Indeed, interacting with others requires the ability to encode their current focus of attention in order to predict their future actions. Previous studies showed that when asked to detect or identify a target, people are faster if shown a gaze oriented toward rather than away from that target. Most important, there is evidence that the emotion conveyed by the face with the averted gaze matters. We further tested the interplay between gaze and face emotion in the context of manipulable objects to understand whether and to what extent other people's gaze influences our own actions toward objects. Participants judged whether a target graspable object was upright or inverted after viewing a face cue with a central or averted gaze. Importantly, the target's handle could be oriented toward the gazed-at location or the opposite side such that gaze and handle were corresponding or non-corresponding in space. Furthermore, we manipulated the expression of the cue by using neutral and fearful faces. Results showed a handle-response compatibility effect (i.e., a facilitation when the response key is on the same side as the object's handle) only with fearful cues with a central gaze.